Generating Short‐Chain Sulfur Suitable for Efficient Sodium–Sulfur Batteries via Atomic Copper Sites on a N, O‐Codoped Carbon Composite. Issue 26 (3rd June 2021) - Xiao, Fengping; Wang, Hongkang; Xu, Jun; Yang, Wenqi; Yang, Xuming; Yu, Denis Y. W.; Rogach, Andrey L.
Abstract: Sodium–sulfur batteries have attracted attention due to their high energy capacities and low costs, but the dissolution of sodium polysulfides still severely affects their cycle life, limiting their real‐world applications. Herein, a stable sulfur host is reported, based on a N, O‐codoped carbon composite derived from a bimetallic Cu–Zn metal‐organic framework, which ensures high sulfur loading (67 wt%). Most importantly, this composite also includes single‐atom copper catalysts, with a high Cu loading of 8.03 wt%. Solid‐state nuclear magnetic resonance, synchrotron X‐ray absorption spectroscopy, and single‐crystal X‐ray diffraction analysis show that single atoms of Cu are coordinated with two N and two O atoms within the produced composite material. Those copper sites can weaken SS bonds in the S8 ring structure, and thus are able to catalyze the formation of short‐chain sulfur molecules in even larger‐size pores. In addition, Cu atoms facilitate the conversion between the short‐chain sulfur and Na2 S. As a result, when the produced sulfur‐loaded carbon framework containing the atomic Cu catalyst is used as a cathode for sodium–sulfur batteries, it exhibits superior capacity of 776 mAh g –1 with a high sulfur utilization (1158 mAh gs –1 normalized with sulfur content) after 100 cycles at 0.1 A g –1, and an excellent rate performance of 483 mAh g –1 (720 mAh gs –1 ) at 5 A g –1 . Abstract : A stable sulfur host is reported, based on a N, O‐codoped carbon composite derived from a bimetallic Cu–Zn metal‐organic framework, which ensures high sulfur loading. This composite also includes single‐atom copper catalysts, with a high Cu loading of 8 wt%. This catalyst enables formation of short‐chain sulfur molecules in even larger‐size pores, and facilitates the conversion between short‐chain sulfur and Na2 S.